LIVE ORAL STORYTELLING IN ?óÔé¼?ôMIDNIGHT SUN AND OTHER STORIES?óÔé¼?Ø - Suwarti Sri Suwarti (ETERNAL (English Teaching Journal), 2010)
Abstract Teaching is considered as an art. Art is closely related to enjoyment and entertainment. There are a lot of efforts should be done to attain the good result of learning. Storytelling can be used as one of forms in teaching in joyfulness. It can be given to the students of all ages at all levels of English proficiency. Live oral storytelling is interesting since the listeners not only can interpret but also express the facial expression and the gestures the storyteller makes. ?óÔé¼?ôMidnight sun and other stories?óÔé¼?Ø written by Wisnubroto Widiarso published by Kanisius can be used as the alternative in choosing live oral storytelling materials. These stories are meant not only to give readers or listeners knowledge about the difference between Indonesian and Western cultures but also the abilities in four language skills, especially listening one. They can arouse the student?óÔé¼Ôäós interest since they express the real life. The teacher can attract the student to be in a warm teaching and learning activities. Teacher as a storyteller should be dynamic and creative in searching the interesting stories. Meanwhile publisher should publish the qualified stories. The student motivates himself to enlarge their knowledge by having reading and listening habit.